A Gender-Responsive Policy Implementation Model for Strengthening Household Economies in the Bajo Community of Wakatobi - Surni Surni; La Ode Achmad Suherman; Jama Toyo; Yulis Yulis (SAINTIS Publishing, 2025)
This study aims to analyze the implementation of women’s empowerment policies in the maritime Bajo community of Wakatobi Regency and to formulate a gender-responsive policy model based on local wisdom. The background of this study lies in the high rate of extreme poverty in Wakatobi, which reached 15.01 percent according to BPS (2022), as well as the strategic role of Bajo women who bear multiple burdens as household managers and family economic supporters. A qualitative case study approach was employed, involving in-depth interviews, participatory observations, and Focus Group Discussions (FGDs) with Bajo women leaders, village officials, and non-governmental partners. The findings reveal that empowerment programs such as the Family Hope Program (PKH), micro-business skills training, and small-scale capital schemes have been implemented, yet remain largely consumptive-oriented and have not sufficiently enhanced sustainable capacity. The main barriers identified include low education levels, limited local government resources, and strong patriarchal culture, while supporting factors are the presence of local female leaders, social solidarity among women, and support from non-governmental organizations. Analysis using the Van Meter and Van Horn model produced a framework for a more gender-responsive policy implementation that emphasizes policy standard refinement, resource strengthening, participatory communication, active involvement of women, and adaptation to local wisdom. This study concludes that empowering Bajo women requires inclusive, participatory, and locally grounded policies to improve family welfare while strengthening the social position of women in coastal communities.